RESULTS OF LOCAL ELECTIONS IN HARGHITA COUNTY, SEPTEMBER 27, 2020 - George-Bogdan TOFAN; Adrian NIŢĂ (Revista Română de Geografie Politică)
The results of the local elections in Harghita County, 27th September 2020. This study aims to faithfully depict the territorial distribution of the electoral decisions taken by the inhabitants of Harghita County at the local elections held on 27th September 2020. Based on official statistical data from the Central Electoral Office (https://locale2020.bec.ro/rezultate), the voting for mayors, local and county councilors, as well as president of Harghita County Council was thoroughly examined. 67 mayors were elected in the 21st Electoral District ‒ Harghita County, their political affiliation being as follows: DUHR (48), SDP (7), HAT (5), IC (5), FHP (1) and NLP (1). Of the 835 local councilor seats, most were won by DUHR (570), followed by HAT (138), SDP (49), NLP (34), FHP (14), CI (13), PMP (8), SRU-LUSP (3), PRO ROMÂNIA (2), while the Magyar Civic Party, National Unity Block, Humanist Power Party (Social-Liberal) and the Liberal and Democrat Alliance won a single seat each. Harghita County Council is comprised of 30 county councilors (with one less seat than in the 2016-2020 legislature), 19 being DUHR members, 4 HAT, 3 SDP, 2 FHP and 2 NLP. Borboly Csaba, the DUHR candidate, received a total of 69 822 votes (64.54% of the votes), thus winning his fourth term as president of Harghita County Council.